2018
DOI: 10.5465/annals.2016.0045
|View full text |Cite
|
Sign up to set email alerts
|

Developing, Sustaining, and Maximizing Team Effectiveness: An Integrative, Dynamic Perspective of Team Development Interventions

Abstract: Organizations regularly make significant investments to ensure their teams will thrive, through interventions intended to support their effectiveness. Such team development interventions (TDIs) have demonstrated their value from both a practical and empirical view, through enabling teams to minimize errors and maximize expertise and thereby advance organizational gains. Yet, on closer examination, the current state of the TDI literature appears so piecemeal that the robustness of extant scientific evidence is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 214 publications
1
97
0
3
Order By: Relevance
“…In our review, there are a number of team training methods identified as effective, particularly cross-training. Others include team coordination training, and team self-correction, and these methods have been shown to impact a variety of team processes involving task work and teamwork factors (Shuffler et al, 2018). It can be surmised that many of the outcomes related to these techniques could apply to HATs.…”
Section: Where To Go Next: Meta-research Themesmentioning
confidence: 99%
“…In our review, there are a number of team training methods identified as effective, particularly cross-training. Others include team coordination training, and team self-correction, and these methods have been shown to impact a variety of team processes involving task work and teamwork factors (Shuffler et al, 2018). It can be surmised that many of the outcomes related to these techniques could apply to HATs.…”
Section: Where To Go Next: Meta-research Themesmentioning
confidence: 99%
“…According to Shuffler et al [19] team building interventions, such as the ones reviewed here, are often judged subjectively by collecting data on participants perceptions of the interventions value. However, in order to fully understand if interventions are successful, more objective measures are needed.…”
Section: Measuring Outcomesmentioning
confidence: 99%
“…Studies also illustrated the need to involve team members in the development of interventions. Effective team building interventions ensure that team members contribute their knowledge of the team's needs to inform the design of the intervention [19]. Four interventions in this review engaged with participants as part of the development stage of their intervention to ensure the intervention was grounded in reality of the participants work environment [43,[46][47][48].…”
Section: Levels Of Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because leadership activities may influence multiple team emergent states at once, it is fundamental to take a systems view (Sterman, 2000) of how the various states affect the rates of increase and decrease to TLC. It is when leaders are conscious of their influence on emergent states as a system that they come to realize that their interventions can simultaneously affect the various parts of the system in distinct ways (Shuffler et al, 2018), or that their interventions can have little impact because of the inertia found in the system (Ericksen and Dyer, 2004). A focus on one particular emergent state to the exclusion of others is often why practices intended to help wind up being net negative (Sterman, 2000).…”
Section: Introductionmentioning
confidence: 99%